2016
DOI: 10.1074/jbc.m116.751867
|View full text |Cite
|
Sign up to set email alerts
|

An Intrinsically Disordered APLF Links Ku, DNA-PKcs, and XRCC4-DNA Ligase IV in an Extended Flexible Non-homologous End Joining Complex

Abstract: DNA double-strand break (DSB) repair by non-homologous end joining (NHEJ) in human cells is initiated by Ku heterodimer binding to a DSB, followed by recruitment of core NHEJ factors including DNA-dependent protein kinase catalytic subunit (DNA-PKcs), XRCC4-like factor (XLF), and XRCC4 (X4)-DNA ligase IV (L4). Ku also interacts with accessory factors such as aprataxin and polynucleotide kinase/phosphatase-like factor (APLF). Yet, how these factors interact to tether, process, and ligate DSB ends while allowing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
94
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
5

Relationship

5
5

Authors

Journals

citations
Cited by 67 publications
(100 citation statements)
references
References 74 publications
(128 reference statements)
6
94
0
Order By: Relevance
“…We describe factors affecting MRN functions at DSBs, stalled RFs, dysfunctional telomeres, and complexes combating exogenous viral DNA infection. We discuss how MRN acts more as a dynamic molecular machine for the expeditious formation of protein–nucleic acid functional scaffolds at DSBs, RFs, dysfunctional telomeres, and viral DNA than as part of linear pathways, as also proposed for nonhomologous end joining (NHEJ) complexes (24). As a multifunctional macromolecular machine, the structural biochemistry of the MRN complex initiates sensing of stalled forks and DSBs, cell cycle checkpoint signaling cascades, incision for and commitment to break repair pathways, reestablishment of posttranslational phosphorylations via ATM kinase, and functional regulation of chromatin remodeling.…”
Section: Introductionmentioning
confidence: 99%
“…We describe factors affecting MRN functions at DSBs, stalled RFs, dysfunctional telomeres, and complexes combating exogenous viral DNA infection. We discuss how MRN acts more as a dynamic molecular machine for the expeditious formation of protein–nucleic acid functional scaffolds at DSBs, RFs, dysfunctional telomeres, and viral DNA than as part of linear pathways, as also proposed for nonhomologous end joining (NHEJ) complexes (24). As a multifunctional macromolecular machine, the structural biochemistry of the MRN complex initiates sensing of stalled forks and DSBs, cell cycle checkpoint signaling cascades, incision for and commitment to break repair pathways, reestablishment of posttranslational phosphorylations via ATM kinase, and functional regulation of chromatin remodeling.…”
Section: Introductionmentioning
confidence: 99%
“…This interaction has been mapped to the periphery of the Ku80 von Willebrand A domain (vWA) 5 . Ku-APLF interaction was shown to facilitate recruitment of the APLF-partner XRCC4 at damaged sites 9 and was proposed to stabilize the assembly of NHEJ factors around the DSB 19 . Notably, an A-KBM-like domain is present at the N-terminus of a recently identified inhibitor of the NHEJ pathway, CYREN(MRI), that also interacts with Ku80 20 (Figure 1a).…”
Section: Introductionmentioning
confidence: 99%
“…This gene is a generally expressed protein of 334 amino acids residues and functions together with DNA ligase IV and DNA-PK in the repair of DNA double-strand breaks. XRCC4 plays an important role in both nonhomologous end joining and the completion of V(D)J recombination [95,96]. Increasing evidence has shown that mutations in XRCC4 can cause short stature, microcephaly, and endocrine dysfunction (SSMED) resulting from more-deicient NHEJ capacity [97,98].…”
Section: The Xrcc4 Gsnps and Afb1-hcc Among Guangxiese Populationmentioning
confidence: 99%